Information security risk management and incompatible parts of organization - Elham Talabeigi; Seyyed Gholamreza Jalali Naeeini (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: we prepared a questionnaire to evaluate Incompatible parts and also risk management in University of Science and Technology E-Learning Center and studying the Incompatible parts impacts on utility of organization. Design/methodology/approach: By using coalitional game theory we present a new model to recognize the degrees of incompatibility among independent divisions of an organization with dependent security assets. Based on positive and negative interdependencies in the parts, the model provides how the organization can decrease the security risks through non-cooperation rather than cooperation. we implement the proposed model of this paper by analyzing the data which have been provided by questionnaires from different three managers' ideas of Iran University of Science and Technology E-Learning Center located in Iran University of Science and Technology, Tehran, Iran. Findings: In general, by collecting data and analyzing them, the survey showed that Incompatible parts of organizations have negative impacts on utility of organization risk management process. Furthermore, it adds values to other organizations and provides the best practices in planning, developing, implementing and monitoring risk management in organizations. Research limitations/implications: Since Information security and also Risk Management are still areas which need to improve in some Iranian universities, we couldn't consider them in our analysis. On the other hand, due to questionnaire limitation, the study's sample size is 1. This size may be considered large for our statistical analysis. Originality/value: The main contribution of this paper is to propose a model for non-cooperation among a number of divisions in a organization and using risk management factors.
Keywords: 650; coalitional game theory; incompatible parts; risk management; security